2021
DOI: 10.2196/28573
|View full text |Cite
|
Sign up to set email alerts
|

Use of Iris Scanning for Biometric Recognition of Healthy Adults Participating in an Ebola Vaccine Trial in the Democratic Republic of the Congo: Mixed Methods Study

Abstract: Background A partnership between the University of Antwerp and the University of Kinshasa implemented the EBOVAC3 clinical trial with an Ebola vaccine regimen administered to health care provider participants in Tshuapa Province, Democratic Republic of the Congo. This randomized controlled trial was part of an Ebola outbreak preparedness initiative financed through Innovative Medicines Initiative-European Union. The EBOVAC3 clinical trial used iris scan technology to identify all health care provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Similarly, the high acceptability rates for return visits aligns with findings in previous studies [22,23], and corroborates the self-reported satisfaction with the initial iris biometric scan in our study participants. Despite the high acceptability, it is noteworthy that the levels of awareness and prior use of biometric iris technologies in most populations remain low and participants express general safety concerns and anxiety about the physical effects biometric scanning could have on eyes [23]. Other reasons for hesitancy in accepting biometric iris identification include privacy and confidentiality concerns among patients and misconceptions about iris scanning [22,23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, the high acceptability rates for return visits aligns with findings in previous studies [22,23], and corroborates the self-reported satisfaction with the initial iris biometric scan in our study participants. Despite the high acceptability, it is noteworthy that the levels of awareness and prior use of biometric iris technologies in most populations remain low and participants express general safety concerns and anxiety about the physical effects biometric scanning could have on eyes [23]. Other reasons for hesitancy in accepting biometric iris identification include privacy and confidentiality concerns among patients and misconceptions about iris scanning [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…These limitations include multiple registration, breach in confidentiality associated with use of names and inaccuracies or errors arising during documentation or verification of personal identifiers [9][10][11][12]14]. Similarly, the high acceptability rates for return visits aligns with findings in previous studies [22,23], and corroborates the self-reported satisfaction with the initial iris biometric scan in our study participants. Despite the high acceptability, it is noteworthy that the levels of awareness and prior use of biometric iris technologies in most populations remain low and participants express general safety concerns and anxiety about the physical effects biometric scanning could have on eyes [23].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, prior to the start of the clinical trial, a pilot study was performed whereby potential participants were interviewed on the feasibility and acceptability of the use of a biometric iris scanning tool for participant identification during the trial and the use of telephone messaging with visit reminders for participant adherence. 27…”
Section: Study Interventionmentioning
confidence: 99%